You have to be trained to start a business, then have regular guidance - Pedrick, Clare (Technical Centre for Agricultural and Rural Cooperation, 2019)
For young agricultural entrepreneurs with ideas, crossgenerational or intra-generational mentorship and training can help to validate initial business concepts and avoid early mis-steps for start-ups.